Familia e internet : consideraciones sobre una relación dinámica (2014)
ABSTARCT: This paper presents the changes in family dynamics, attributed by family members to their use of Internet. Such attributed changes are associated to family member’s individual experience using Internet and the interactions with other family members. A qualitative analysis of one of the research categories related to the study named “Uses and meanings of digital technologies in families with teenagers in Medellín city” is presented. The method used in the study is the analysis of the experiences described by family members, specifically by parents and teenagers. In this study, 9 parents and 25 teenagers participated in interviews and focus groups, and also surveys were conducted with 141 parents and 226 teenagers. The results show that, depending on parent’s Internet literacy, particular interaction forms between teenagers and them are established.